Prospectus of Salary/Wage Subsidy Policy for Worker Welfare Improvement During Covid-19 Pandemic - Nadhiva Putri Aprilia; Kadek Cahya Susila Wibawa (Jurnal IUS Kajian Hukum dan Keadilan, 2021)
Indonesia officially stipulates Corona Virus Disease 2019 (Covid-19) as a health emergency with the issuance of Presidential Decree No. 11 of 2020. The employment sector is affected by the Covid-19 pandemic. The government issued PMK (Minister of Manpower Regulation) No. 14 of 2020 as an effort to realize the national economic recovery program and improve worker welfare. This law writing aims to analyze the urgency and implementation of the policy of providing salary/wage subsidies for workers affected by Covid-19 and to find out the existence (prospectus) of the policy in the future.This research is a doctrinal law research with a conceptual approach and statute approach. The researchers conducted an analysis of secondary data, both in the form of primary legal materials, secondary legal materials, and tertiary legal materials. The analysis was carried out in a descriptive-qualitative. The results of the research showed that the salary/wage subsidy policy was implemented with the applicable terms and conditions as stipulated in PMK No. 14 of 2020. In the implementation, the policy was aligned with the participation of workers in the BPJS Employment. This policy is a fairly appropriate solution related to the economic recovery of the community during a pandemic. Itcan be a model for similar policy making in facing pandemic in the future